HUBUNGAN SOFT SKILS DENGAN KEPEMIMPINAN KEPALA SEKOLAH TAMAN KANAK KANAK SE KECAMATAN TAMPAN PEKANBARU - Imelda Dewi Maliza Imelda Dewi Maliza; Wilson '; Ria Novianti Ria Novianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract. Phenomenon which occurs in the majority of kindergarten principal in district Tampan Pekanbaru City aresome headmasters arelessin motivatingthe teachers so that teachers can not give maximum performance, there is still difficultyof kindergarten headmasterif they are requested direction and advice, and there is still kindergarten principal less firmly in giving warning for errors made by the teachers. The purpose of this study is to describe the soft skills and leadership of the principal, and determine the relationship between soft skills by kindergarten school leadership in District of Tampan Pekanbaru City. Respondents in this study amounted to 42 people. Data collection techniques used by questionnaire and observation. The data analysis technique used is descriptive quantitative statistical data processing (SPSS). From the research results obtained are positive and significant relationship between soft skills by kindergarten school leadership inDistrict Of Tampan Pekanbaru. It can be seen from rhit value = 0.811 and p = 0.000. Therefore p <0.05 (0.000 <0.05), then Ho is rejected. In addition, the hypothesis test "t test", the result thit = 8.843 and the value ttab (5%) (df = n - 2 = 42-2 = 40) = 2.000. Because thit> ttab (8.843> 2.000), it means that there is a positive and significant relationship between soft skills with school leadership. The resulting determinant coefficient is r2 (0.8112) = 0.657, it can be seen that the influence of soft skills for 65.7% of the kindergarten school leadership. The level of correlation between the soft skills and school leadership is in very highcategory with a correlation coefficient 0.811. Keyword : soft skills, school leadership